Tumor Microenvironment-Based Risk Stratification of Oropharyngeal Squamous Cell Carcinoma - Almangush, Alhadi; Jouhi, Lauri; Haglund, Caj; Hagström, Jaana; Mäkitie, Antti A.; Leivo, Ilmo (Wiley, 2025)
BACKGROUND: Evaluation of the prognostic impact of tumor microenvironment (TME) has received attention in recent years. We introduce a TME-based risk stratification for oropharyngeal squamous cell carcinoma (OPSCC).
MATERIAL AND METHODS: A total of 182 patients treated for OPSCC at the Helsinki University Hospital were included. TME-based risk stratification was designed combining tumor-stroma ratio and stromal tumor-infiltrating lymphocytes assessed in hematoxylin and eosin-stained sections.
RESULTS: In multivariable analysis, TME-based risk stratification associated with poor disease-free survival with a hazard ratio (HR) of 2.68 (95% CI 1.11-6.48, p = 0.029). In addition, the proposed risk stratification was associated with poor disease-specific survival (HR 2.687, 95% CI 1.28-5.66, p = 0.009) and poor overall survival (HR 2.21, 95% CI 1.23-3.99, p = 0.008).
CONCLUSION: Our TME-based risk stratification provides a powerful prognostic tool that can be used in daily treatment planning of OPSCC together with tumor-related prognostic markers.